Influence of human chorionic gonadotropin (hCG) on in vitro growth of Plasmodium falciparum - Pong, Clinton K (BioMed Central, 2009)
BACKGROUND: During pregnancy, women are more susceptible to Plasmodium falciparum infections and frequently have a higher parasitaemia than non-pregnant women. Several mechanisms are responsible for their increased susceptibility, including down-modulation of immune responses that aid in parasite clearance and sequestration of infected erythrocytes in the placenta. Early in pregnancy, a third mechanism may contribute to higher parasitaemia, since it has been reported that addition of human chorionic gonadotropin (hCG) to in vitro cultures of the NF54-strain of P. falciparum results in increased parasite growth rates. The goal of this study was to further examine the effect of hCG on P. falciparum growth. METHODS: The NF54-3D7, FVO and 7G8 strains of P. falciparum were cultured in vitro with various physiological concentrations of hCG purchased from three sources. Infected erythrocytes were also co-cultured with a human cell line that naturally secretes hCG. RESULTS: Results from 14 experiments using different combinations of parasite strains and concentrations of hCG from different sources, as well as the co-culture studies, failed to provide convincing evidence that hCG enhances parasite growth in vitro. CONCLUSION: Based on these data, it seems unlikely that hCG has a direct effect on the rate of parasite growth early in pregnancy.